Childhood B-Cell Acute Lymphoblastic Leukemia Following SARS CoV-2 Infection: A Potential Second "Hit" in Leukemogenesis. Issue 8 (23rd November 2021) - Persaud, Yogindra; Shamoun, Mark; Chitlur, Meera; Des Rosier, Kyle J.; Taub, Jeffrey W.
Abstract : The Coronavirus Disease 2019 (COVID-19) pandemic has become the worst pandemic in modern history. The lack of prior immunity to the virus has resulted in a high mortality rate, though children have fared better than adults, overall. We present a case of a child who developed B-cell acute lymphoblastic leukemia 1 week following a symptomatic COVID-19 infection. It is possible that this viral infection provided the "second hit" posited to occur in pediatric leukemogenesis as proposed by Dr Greaves, with his initial viral exposure occurring several weeks earlier.